2019
DOI: 10.46281/ijafr.v4i2.442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Ownership Structure on the Financial Performance of Banks: Comparative Study between Conventional and Islamic Banks

Abstract: According to the literature of corporate governance, ownership structure is advanced as a non-dissociable mechanism of control intended to follow the stakeholders and especially used by shareholders to monitor the conflicts of interest and the opportunistic behavior of managers. Several previous studies have focused on the impact of ownership structure on financial performance separately in conventional or in Islamic banks. However, the comparative studies between these two impacts are non-existent. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In 2017 another study showed their empirical study that the banking sector was the highest efficiency level but the efficiency level was shut down in 2010 for scale and global financial crisis effects (Banna, Ahmad, & Koh, 2017). Haddad et al (2019) found a positive relationship has existed between ownership structure and bank performance. To find this result the study conducted by an analysis Ordinary Least Square method on two groups of data set such as 63 conventional banks and 63 Islamic banks from 16 countries.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…In 2017 another study showed their empirical study that the banking sector was the highest efficiency level but the efficiency level was shut down in 2010 for scale and global financial crisis effects (Banna, Ahmad, & Koh, 2017). Haddad et al (2019) found a positive relationship has existed between ownership structure and bank performance. To find this result the study conducted by an analysis Ordinary Least Square method on two groups of data set such as 63 conventional banks and 63 Islamic banks from 16 countries.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…ALM is also regarded as an essential tool banks use to conduct risk management activities such as market risk, financial risk, interest rate risk, and others (Fabozzi & Konishi, 1991). It is responsible for performing economic activities such as risk management of liquidity, project planning, trading, growth projection, capital planning, funding, and market risks (Adebisi et al, 2020;Haddad et al, 2019;Riyazahmed & Baranwal, 2021). The ALM practices are implemented through a three-tier structure:  ALM information system,  ALM organization (structure and responsibilities) and  ALM process (recognizing risks, estimation, administration, and setting of policies) (Chaturvedi, 2014;Jayanthi & Umarani, 2014;Joshi & Sontakay, 2017;Singh, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As result, banking system problems in a nation's economy will result in eroding the overall economy of that nation (Morris & Turner, 1996). AML as a responsible unit in a bank performs different types of functions, for example, the risk associated with liquidity management, trading, forecasting for planning projects, funding, making plans for the size of capital, and risk arising due to market changes (Haddad et al, 2019;Adebisi et al, 2020). It is the process to formulate strategies and plans for maintaining, implementing, and monitoring the firm's assets and liabilities (obligation).…”
Section: Introductionmentioning
confidence: 99%